Dribbling Skill Level in Football Game - Handoko Sejahtera Sigalingging; Dicky Hendrawan (Journal of Football Research, 2024)
This research was carried out with the aim of knowing the level of dribbling skills in the soccer game of class X students of SMK Negeri 1 Siatas Barita Kab. North Tapanuli Academic Year 2020/2021. The subjects in this study were students of class X, amounting to 27 people. This research is a quantitative descriptive study that is about students' dribbling skills, meaning that in this study researchers only wanted to know the level of dribbling skills of class X students at SMK Negeri 1 Siatas Barita Kab. North Tapanuli for the 2020/2021 Academic Year, where the data is in the form of numbers in seconds. The results showed that the level of dribbling skills of class X SMK Negeri 1 Siatas Barita Kab. North Tapanuli for the 2020/2021 Academic Year are as follows: there are no students (0%) who are included in the "very high" dribbling skill category, there are 8 students (29.63%) who are included in the "high" dribbling skill category, while 12 students (44.44%) were included in the "adequate" dribbling skill category, there were 4 students (14.82%) included in the "low" dribbling skill category, and the sis there were 3 students (11.11%) included in the category of “very low” dribbling skills. The mean value of 17.84 lies in the interval 20.97 16.78, The conclusion that can be drawn is the level of dribbling skills of class X SMK Negeri 1 Siatas Barita Kab. North Tapanuli for the 2020/2021 Academic Year is included in the "enough" category, which is 12 students (44.44%) of the total 27 students.